Applying an Evolutionary Approach of Risk-Taking Behaviors in Adolescents - Salas-Rodríguez, Javier; Gómez-Jacinto, Luis; Hombrados-Mendieta, Isabel; del Pino-Brunet, Natalia (Frontiers in Psychology, 2022)
Risk-taking behaviors in adolescents have traditionally been analyzed from a psychopathological approach, with an excessive emphasis on their potential costs. From evolutionary theory we propose that risk-taking behaviors can be means through which adolescents obtain potential benefits for survival and reproduction. The present study analyzes sex differences in three contexts of risk (i.e., risk propensity, expected benefits and risk perception) in the evolutionary specific domains and the predictive value of these domains over risk-taking behaviors, separately in female and male adolescents. 749 adolescents (females = 370) valued their risk perception, expected benefits and risk propensity through the Evolutionary Domain-Specific Risk Scale, as well as their engagement in risk-taking behaviors through the Risky Behavior Questionnaire. Male adolescents showed lower risk perception in two evolutionary domains, expected higher benefits in two other domains and showed higher risk propensity in six domains. Female adolescents showed lower risk perception in two domains. Additionally, risk perception, expected benefits and risk propensity in the evolutionary domains predicted the engagement in risk-taking behaviors in male adolescents, whereas in female adolescents only expected benefits and risk propensity showed a predictive effect over risk-taking behaviors. These results suggest the potential role of evolutionary mechanisms on risk-taking behaviors in adolescents. Results have practical implications for interventions programs aimed at reducing risk-taking behaviors. In addition to considering sex differences, intervention programs should consider alternative behaviors through which adolescents can reach their evolutionary goals, and handle the risks related to those behaviors that cannot be replaced but have potential benefits for adolescents.